Post-weaning diarrhea in pigs from a single Danish production herd was not associated with the pre-weaning fecal microbiota composition and diversity - Rydal, Martin Peter; Gambino, Michela; Castro-Mejia, Josue L.; Poulsen, Louise Ladefoged; Jørgensen, Claus Bøttcher; Nielsen, Jens Peter (Frontiers in Microbiology, 2023)
The association between the porcine pre-weaning gut microbiota composition and diversity, and subsequent post-weaning diarrhea (PWD) susceptibility is currently being studied. In this longitudinal study, we examined the association between pre-weaning fecal microbiome composition and diversity, and PWD development in a Danish sow herd. Forty-five pigs were followed from birth until seven days after weaning (post-natal day (PND) 33). At PND 33, the pigs were categorized as PWD cases or healthy controls based on fecal consistency. We compared their fecal microbiomes at PND 8, late lactation (PND 27) and seven days post weaning (PND 33) using 16S rRNA V3 region high-throughput sequencing. At PND 27 and 33, we also weighed the pigs, assessed fecal shedding of hemolytic E. coli by culture and characterized hemolytic isolates by ETEC virulence factors with PCR and by whole genome sequencing. A total of 25 out of 45 pigs developed PWD and one Enterotoxigenic E. coli strain with F18:LT:EAST1 virotype was isolated from most pigs. At PND 33, we found differences in beta diversity between PWD and healthy pigs (R2=0.027, p=0.009) and that body weight was associated with both alpha and beta diversity. Pre-weaning fecal microbiome diversity did not differ between PWD and healthy pigs and we found no significant, differentially abundant bacteria between them. In the production herd under study, pre-weaning fecal microbiome diversity and composition were not useful indicators of PWD susceptibility.